Arterial Hypotension Following Norepinephrine Decrease in Septic Shock Patients Is Not Related to Preload Dependence: A Prospective, Observational Cohort Study - Andrei, Stefan; Nguyen, Maxime; Abou-Arab, Osama; Bouhemad, Belaid; Guinot, Pierre-Grégoire (Frontiers in Medicine, 2022)
Background The optimal management of hypotensive patients during norepinephrine weaning is unclear. The primary study aim was to assess the ability of preload dependence to predict hypotension following norepinephrine weaning. The secondary aims were to describe the effect of norepinephrine weaning on preload dependence, and the cardiovascular effects of fluid expansion in hypotensive patients following norepinephrine weaning. Materials and Methods This was a prospective observational monocentric study. We included PiCCO®-monitored patients with norepinephrine-treated septic shock, for whom the physician decided to decrease the norepinephrine dosage during the de-escalation phase. Three consecutive steps were evaluated with hemodynamic measurements: baseline, after norepinephrine decrease, and after 500 mL fluid expansion. Results Forty-five patients were included. Preload dependence assessed by stroke volume changes following passive leg raising was not predictive of pressure response to norepinephrine weaning [AUC of 0.42 (95%CI: 0.25–0.59, p = 0.395)]. After fluid expansion, there was no difference in the prior preload dependence between pressure-responders and non-pressure-responders (14 vs. 13%, p = 1). The pressure response to norepinephrine decrease was not associated with pressure response after fluid expansion (40 vs. 23%, p = 0.211). Conclusion Hypotension following norepinephrine decrease was not predicted by preload dependence, and there was no association between arterial hypotension after norepinephrine decrease and fluid response.